2017
DOI: 10.1096/fj.201601064r
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin association with T‐cadherin protects against neointima proliferation and atherosclerosis

Abstract: Adiponectin, an adipocyte-derived protein abundant in the circulation, is thought to be protective against atherosclerosis. However, it is not fully understood how the association of adiponectin with vascular cells and its antiatherogenic effect are connected. In this study, T-cadherin was essential for accumulation of adiponectin in the neointima and atherosclerotic plaque lesions, and the adiponectin-T-cadherin association protected against vascular injury. In the apolipoprotein E-knockout (ApoE-KO) mice, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 58 publications
2
76
0
Order By: Relevance
“…Recent studies have shown that the active forms, multimeric and hexameric adiponectin, accumulate in tissues such as heart, vascular endothelium, and skeletal muscles through interaction with T-cadherin, a unique glycosylphosphatidylinositol-anchored (GPI-anchored) cadherin (7)(8)(9). Importantly, we recently showed that adiponectin suppressed neointimal and atherosclerotic plaque formations through T-cadherin (10). Other groups have also shown the significance of adiponectin/T-cadherin association in cardiovascular protection (7,8).…”
Section: Introductionmentioning
confidence: 75%
“…Recent studies have shown that the active forms, multimeric and hexameric adiponectin, accumulate in tissues such as heart, vascular endothelium, and skeletal muscles through interaction with T-cadherin, a unique glycosylphosphatidylinositol-anchored (GPI-anchored) cadherin (7)(8)(9). Importantly, we recently showed that adiponectin suppressed neointimal and atherosclerotic plaque formations through T-cadherin (10). Other groups have also shown the significance of adiponectin/T-cadherin association in cardiovascular protection (7,8).…”
Section: Introductionmentioning
confidence: 75%
“…Since leptin, a central regulator of food intake and energy expenditure, was demonstrated to be an adipose-specific adipokine, great attention has been given to the identification and characterization with the tethering molecule T-cadherin, APN accumulates in the vascular wall. 29 These in vivo data suggest that APN protects against various obesity-inducible vascular diseases such as atherosclerosis, vascular dysfunction, and hypertension by its interaction with vascular component cells.…”
Section: Role Of Adipokines In Vascular Diseasesmentioning
confidence: 96%
“…The adiponectin-mediated production of exosomes also may also affect whole-body glucose metabolism. tion by adiponectin may require T-cadherin and consumption of adiponectin through T-cadherin binding (14)(15)(16)98). Low tissue T-cadherin and/or low T-cadherin-mediated consumption of adiponectin may result in poor CHF prognosis.…”
Section: Adiponectin Regulates Systemic Exosome Level Through T-cadherinmentioning
confidence: 99%
“…As we discuss below, organ protec- Clinical analyses have demonstrated that HMW multimeric adiponectin is the active form, and it exerts various pleiotropic effects (64)(65)(66)(67). Recent studies have shown that the active HMW multimers and hexamers of adiponectin accumulate in tissues such as heart, vascular endothelium, and skeletal muscles through interaction with T-cadherin (14)(15)(16)(17)98). Plasma adiponectin increased more than 3-fold in T-cadherin-KO mice compared with WT mice, with a dramatic increase of HMW multimeric adiponectin (98).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
See 1 more Smart Citation